The Evolution of Teleophthalmology Programs in the United Kingdom: Beyond Diabetic Retinopathy Screening. (March 2016) - Sim, Dawn A.; Mitry, Danny; Alexander, Philip; Mapani, Adam; Goverdhan, Srini; Aslam, Tariq; Tufail, Adnan; Egan, Catherine A.; Keane, Pearse A.
Modern ophthalmic practice in the United Kingdom is faced by the challenges of an aging population, increasing prevalence of systemic pathologies with ophthalmic manifestations, and emergent treatments that are revolutionary but dependent on timely monitoring and diagnosis. This represents a huge strain not only on diagnostic services but also outpatient management and surveillance capacity. There is an urgent need for newer means of managing this surge in demand and the socioeconomic burden it places on the health care system. Concurrently, there have been exponential increases in computing power, expansions in the strength and ubiquity of communications technologies, and developments in imaging capabilities. Advances in imaging have been not only in terms of resolution, but also in terms of anatomical coverage, allowing new inferences to be made. In spite of this, image analysis techniques are still currently superseded by expert ophthalmologist interpretation. Teleophthalmology is therefore currently perfectly placed to face this urgent and immediate challenge of provision of optimal and expert care to remote and multiple patients over widespread geographical areas. This article reviews teleophthalmology programs currently deployed in the United Kingdom, focusing on diabetic eye care but also discussing glaucoma, emergency eye care, and other retinal diseases. We examined current programs and levels of evidence for their utility, and explored the relationships between screening, teleophthalmology, disease detection, and monitoring before discussing aspects of health economics pertinent to diabetic eye care. The use of teleophthalmology presents an immense opportunity to manage the steadily increasing demand for eye care, but challenges remain in the delivery of practical, viable, and clinically proven solutions.